Correlates of Coronavirus Disease 2019 (COVID-19) Vaccine Hesitancy Among People Who Inject Drugs in the San Diego-Tijuana Border Region. (22nd November 2021) - Strathdee, Steffanie A; Abramovitz, Daniela; Harvey-Vera, Alicia; Vera, Carlos F; Rangel, Gudelia; Artamonova, Irina; Patterson, Thomas L; Mitchell, Rylie A; Bazzi, Angela R
Abstract: Background: People who inject drugs (PWID) are vulnerable to acquiring severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We examined correlates of coronavirus disease 2019 (COVID-19) vaccine hesitancy among PWID in the US-Mexico border region, of whom only 7.6% had received ≥ 1 COVID-19 vaccine dose by September 2021. Methods: Between October 2020 and September 2021, participants aged ≥ 18 years from San Diego, California, USA, and Tijuana, Baja California, Mexico, who injected drugs within the last month completed surveys and SARS-CoV-2, human immunodeficiency virus (HIV), and hepatitis C virus (HCV) serologic testing. Logistic regressions with robust standard error estimation via generalized estimating equations identified factors associated with being unsure or unwilling to receive COVID-19 vaccines. Results: Of 393 participants, 266 (67.7%) were willing to receive COVID-19 vaccines and 127 (32.3%) were hesitant (23.4% unwilling and 8.9% unsure). Older participants, those with greater food insecurity, and those with greater concern about acquiring SARS-CoV-2 were more willing to be vaccinated. Higher numbers of chronic health conditions, having access to a smart phone or computer, and citing social media as one's most important source of COVID-19 information were independently associated with vaccine hesitancy. COVID-19-related disinformation was independently associated with vaccine hesitancy (adjusted odds ratio: 1.51 per additional conspiracy theory endorsed; 95% confidence interval: 1.31–1.74). Conclusions: Nearly one third of people injecting drugs in the US-Mexico border region were COVID-19 vaccine hesitant, which was significantly associated with exposure to social media, disinformation and co-morbidities and inversely associated with food security and high perceived threat of COVID-19. Interventions that improve accurate knowledge of and trust in COVID-19 vaccines are needed in this vulnerable population. Abstract : Nearly one third of people injecting drugs in the US-Mexico border region were COVID-19 vaccine hesitant, which was significantly associated with exposure to social media, disinformation and co-morbidities and inversely associated with food security and high perceived COVID-19 threat.